Physiotherapy in Respiratory Care / A Problem-Solving Approach to Respiratory and Cardiac Management - Hough Alexandra (Stanley Thornes (Publishers) Ltd, 1996)
The bulk of the book is devoted to physiotherapy management and its rationale, based on the three main problems: reduced lung volume, breathlessness and sputum retention. Preface, Acknowledgements, Assessment of the Respiratory Patient, Respiratory Disorders, General Management, Physiotherapy Management, Management of Breathlessness and Pulmonary Rehabilitation, Physiotherapy for Specific Groups of People, Intensive Care, Physiotherapy in Intensive Care, Conditions in Intensive Care, Physiotherapy for Children and Infants, Evaluation of Chest Physiotherapy, Glossary of Definitions and Abbreviations and Symbols and Normal Values, Further Reading, References, Index.